Two new members in the Contracaecum osculatum complex (nematoda, ascaridoidea) from the Antarctic - P. Orecchia; J. Plotz; P. Arduino; MATTIUCCI, Simonetta; D'AMELIO, Stefano; PAGGI, Lia; CIANCHI, Maria Rossella; NASCETTI, Giuseppe; BULLINI, Luciano (International Journal for Parasitology, 1994)
The genetic structure of adults and larvae of Contracaecum osculatum (sensu lato) from the Antarctic is analyzed on the basis of 24 enzyme loci. Significant deviations of genotype frequencies from the Hardy-Weinberg equilibrium were found, even in samples recovered from the same host. These data indicate that two distinct, reproductively isolated species coexist in C. osculatum (sensu lato) samples from the Antarctic. They were provisionally designated C. osculatum D and E, as they do not correspond to any of the three species previously detected in this complex from the Atlantic Arctic-Boreal region (C. osculatum A, B and C). An allozyme diagnostic key for the identification of the five members of the C. osculatum complex, at the larval and adult stage and in both sexes, is given. Species D and E were found to be genetically quite variable: average P99 = 84.3, A = 3.3 and H(e) = 0.23. Both showed high values of intraspecific gene flow: Nm = 4.6 and 6.1 respectively; similar values were found for the Arctic-Boreal C. osculatum A, B and C. The most related members of the complex are the Antarctic species E and the Arctic-Boreal species A (D(Nei) = 0.21), while the most differentiated ones are the Arctic-Boreal species B and C (D(Nei) = 0.76). The evolutionary divergence of C. osculatum C started more than 3 million years ago, in a Pliocene refugium (Baltic Sea). As to the other C. osculatum species, their evolutionary divergence took place during Pleistocene, when this complex achieved a bipolar distribution. This process involved two distinct colonizations of the marine Antarctic region by ancestors of the northern hemisphere, about 1.5 and 1 million years ago, giving origin to C. osculatum D and E respectively.